1984
DOI: 10.1016/0008-6215(84)85029-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the carbohydrate moieties of human tamm-horsfall glycoprotein

Abstract: ABSTRAaGlycopeptides present in a pronase digest of human Tamm-Horsfall glycoprotein were fractionated by chromatography on DEAE-Sephadex A25 in 0.1~ acetic acid. The separated glycopeptides were characterised by 500-MHz 'H-n.m.r. spectroscopy, in conjunction with sugar and amino acid analysis, and they were shown to be of the N-glycosylic, N-acetyllactosamine type. Each fraction consisted mainly of a tetra-antennary entity having various degrees of complexity, with lesser amounts of the triantennary structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…1979;Soh et al, 1980;Afonso et al, 1981;Donald et al, 1982Donald et al, , 1983Williams et al, 1984;Serafini-Cessi et al, 1984a, b;Donald and Feeney, 1986;Dall'Olio et al, 1988;Smagula et al, 1990). Tn the present study the N-linked carbohydrates were enzymically released from T-H glycoprotein of one male donor by PNGase-F, and fractionated into more than 150 fractions by a combination of three liquidchromatographic techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1979;Soh et al, 1980;Afonso et al, 1981;Donald et al, 1982Donald et al, , 1983Williams et al, 1984;Serafini-Cessi et al, 1984a, b;Donald and Feeney, 1986;Dall'Olio et al, 1988;Smagula et al, 1990). Tn the present study the N-linked carbohydrates were enzymically released from T-H glycoprotein of one male donor by PNGase-F, and fractionated into more than 150 fractions by a combination of three liquidchromatographic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the structure has been determined of a Sd" active pentasaccharide cleaved from T-H glycoprotein with endo-P-galactosidase (Donald et al, 1983;Donald and Feeney, 1986). Previous studies on T-H-glycopeptide mixtures have revealed that the Sd" determinant resides in the nonreducing termini of branched N-glycans (Williams et al, 1984). In addition to sialylated compounds, small amounts of oligomannose-type carbohydrates have been reported to occur in the glycoprotein (Afonso et al, 1981;Dall'Olio et al, 1988).…”
mentioning
confidence: 99%
“…THP is known to be a heavily glycosylated protein, with carbohydrates accounting for 30% of the total molecular mass (55). About 80% of the carbohydrate moieties expressed on human THP are of the complex type, with sialylated tri-and tetraantennary structures (37). However, proteolytic digestion of human urinary THP consistently yielded high mannose-bearing glycopeptides.…”
Section: Tamm-horsfall Protein As a Major Urinary Defense Factormentioning
confidence: 99%
“…These studies were, however, not performed in the context of well defined E. coli strains or in the presence of the cognate urothelial receptors. It was also unclear whether THP possesses a single, well conserved, high-mannose chain that is necessary for type 1 fimbrial binding (37,38) and whether soluble urinary THP is capable of interacting at all with the fimbriae (35). There have also been questions regarding the specificity of the THP-E. coli interaction as non-mannose-specific P fimbriae were found to bind THP (39).…”
mentioning
confidence: 99%
“…Furthermore, GalNAc H1 is observed at δ 4.73Ϫ4.76 (42°C), while its NAc signal resonates at δ 2.015Ϫ2.019. Due to the attachment of GalNAc to Gal via a (β1-4) linkage, Gal H4 resonates at δ 4.11Ϫ4.12 and H3 at δ 4.15 (Williams et al, 1984;Donald and Feeney, 1986;Hård et al, 1992).…”
Section: Generalmentioning
confidence: 99%